Improving the Aging Resistance of Asphalt by Addition of Polyethylene and Sulphur - Maria Iqbal; Arshad Hussain; Afaq Khattak; Kamran Ahmad (Salehan Institute of Higher Education, 2020)
With the increase in demand of flexible pavements, due to their various advantages over rigid pavements, there is a need to improve the aging properties of the bitumen in order to enhance its resistance against different types of distresses such as rutting, fatigue cracking. This research focus on the use of one polymeric additive Polyethylene (PE) and one non polymeric additive Sulphur (S) to enhance the aging resistance of asphalt. These modifiers are evaluated for their effect on the aging mechanism in comparison with the unmodified bitumen. Aging of the original and modified bitumen is realized by the Rolling Thin Film Oven (RTFO) and Pressure Aging Vessel (PAV). Physical properties of the aged and unaged asphalt binders are evaluated through empirical testing like penetration, ductility and softening point test. Optimum content of the modifiers is obtained by comparing the results of conventional properties before and after aging. Fourier Transformed Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM) are performed to bring out the chemical and morphological changes in the modified binder. Rheological properties of modified asphalt are evaluated with the help of a Dynamic Shear Rheometer (DSR). Results indicate improvement in physical properties of the modified asphalt even after the aging. Penetration index increased which shows less temperature susceptibility of the modified binders. Carbonyl and sulfoxide index are used as aging indicators which shows reduction in case of modified samples. Decrease in the sulfoxide and carbonyl index indicates better oxidation resistance of the modified samples. Morphological analysis proves good compatibility of the modifiers with asphalt binders. DSR results indicate improved viscoelastic properties of the modified binders. Hence it can be concluded that Polyethylene and Sulphur are good options to improve the aging resistance of asphalt in terms of their cost effectiveness and environment friendly nature.